The Impact of Working with Farm Animals on People with Offending Histories: A Scoping Review - Payne, Libby (International journal of offender therapy and comparative criminology, 2023)
Within the Criminal Justice System, using animals for therapeutic or rehabilitative purposes has garnered momentum and is extensively researched. By contrast, the evidence concerning the impact of farm animal work, either on prison farms or social farms for community sanctions, is less well understood. This review sought to explore the evidence that exists in relation to four areas: (1) farm animals and their contribution to rehabilitation from offending; (2) any indicated mechanisms of change; (3) the development of a human—food/production animal bond, and (4) the experiences of forensic service users working with dairy cattle. Fourteen articles were included in the review. Good quality research on the impact of working with farm animals and specifically dairy cattle, with adult offenders, was very limited. However, some studies suggested that the rehabilitative potential of farm animals with offenders should not be summarily dismissed but researched further to firmly establish impact.